Detection and quantitation of human papillomavirus DNA in peripheral blood mononuclear cells from blood donors. Issue 11 (25th July 2019) - Vergara, Nicolás; Balanda, Monserrat; Vidal, Deyanira; Roldán, Francisco; S. Martín, Héctor; Ramírez, Eugenio
Abstract: Human papillomavirus (HPV) is the etiological agent of cervical cancer. Also, HPV has been associated with anogenital cancer, oropharyngeal cancer, genital warts, and other dermatological diseases. HPV infects epithelial cells and their replication is closely linked to epithelial differentiation. The presence of HPV DNA in peripheral blood mononuclear cells (PBMC) has been reported in some patients with head and neck cancer, cervical cancer, and other genital diseases. However, the presence of HPV DNA in blood in asymptomatic subjects is still unresolved. The objective of this study was to evaluate the presence of HPV DNA in PBMC from asymptomatic blood donors. Blood samples were collected from 207 healthy Chilean blood donors. Genomic DNA was extracted from PBMC and HPV DNA detection was performed by real‐time quantitative polymerase chain reaction assays with GP5+/6+ primers. HPV typing was carried out by genetic sequencing of a 140 to 150 bp fragment of the L1 gene. HPV DNA was detected in 6.8% (14/207) of blood donors. Single HPV infections were detected in seven blood donors. High‐risk HPV was found in 6.3% (13/207) of cases: nine blood donors were infected with HPV‐16, five with HPV‐18, two with HPV‐51, and one case was infected with either 32, 33, 45, 59, 66, 70, or 82. The median viral load value was 21.3 copies/mL blood or 13.4 HPV (+) cells per 10 4 PBMC. These results show that HPV DNA is present in PBMC from healthy blood donors and it suggests that blood could be a new route of HPV dissemination. Highlight: PBMC from 207 healthy Chilean blood donors were analyzed. HPV DNA and high‐risk HPV were detected in 6.8% (14) and 6.3% (13) of blood donors, respectively. Results show that HPV DNA is present in PBMC from blood donors and they suggest blood could be a new route of HPV dissemination.